IJEAST 2021
DOI: 10.33564/ijeast.2021.v06i06.026
|View full text |Cite
|
Sign up to set email alerts
|

Resource-Based View Theory Application on the Educational Service Quality

Abstract: Background and Objectives: The purpose of this study is to review the resource-based view theory on service quality that contribute to and expand internal resources and services of high quality. Several empirical studies have examined how to apply resource-based view theory to exploiting opportunities in higher education. With the help of this resource-based view theory, urban higher education can apply how to obtain and mobilize additional resources or use existing resources more efficiently and effectively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…We contemplate academics' perceptions of the university's tangible and intangible assets and their self-based and skill-based professional identity. The findings are in accordance with the RBT, proposing the tangible and intangible resources as distinctive [90]. However, until now, the RBT has been related mainly to the value of the higher education system and institutions' sustainable competitive advantage [91][92][93], barely suggesting the academics' satisfaction due to the resources' distinction.…”
Section: Discussionsupporting
confidence: 77%
“…We contemplate academics' perceptions of the university's tangible and intangible assets and their self-based and skill-based professional identity. The findings are in accordance with the RBT, proposing the tangible and intangible resources as distinctive [90]. However, until now, the RBT has been related mainly to the value of the higher education system and institutions' sustainable competitive advantage [91][92][93], barely suggesting the academics' satisfaction due to the resources' distinction.…”
Section: Discussionsupporting
confidence: 77%
“…By identifying and leveraging these resources, universities can improve their overall performance and attract more students, faculty, and funding. Some studies have applied the RBV theory to higher education institutions and found that an institution's human capital, such as the quality of faculty and staff, and organizational capital, such as institutional reputation, are critical for achieving a competitive advantage in the education industry (Vasudevan, 2021).…”
Section: Resource-based View Theorymentioning
confidence: 99%
“…In the context of education management, this could include human resources, physical infrastructure, IT infrastructure, and data. Researchers can use RBV to pinpoint the specific IT resources that educational institutions possess or need to acquire to improve HR practices (Vasudevan 2021;Lee and Yun, 2020). Based on this background, the following hypotheses were developed in this study:  H1: IT tools used in HR processes have a positive effect on education management.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…According to Barney's RBV theory of the company from 1991, "key sources of competitive advantage to an organisation are the firm's structure, human capital, which is the skills, judgement, and level of intelligence of the employees, and human resource management systems" (Vasudevan, 2021). According to RBV theory, HRMS may increase competitive advantage via staff development and motivational skills, create distinctive social ties, be firmly ingrained in a company's operational procedures, and contribute to organisational knowledge (Barney, 1991).…”
Section: Resource Based View (Rbv Theory)mentioning
confidence: 99%